SECURITY ISSUES IN BLOCKCHAIN TECHNOLOGY - Zokir Mamadiyarov (International Journal of Artificial Intelligence for Digital Marketing, 2024)
Hailed as a revolutionary innovation, blockchain technology has attracted a lot of attention from various industries due to its decentralized and immutable nature. It serves as the underlying technology for cryptocurrencies such as Bitcoin and Ethereum, providing transparency, decentralization and security. However, blockchain technology is not legally protected from security issues, and potential solutions to address security issues related to blockchain technology are being discussed . Overall, this article provides an overview of blockchain technology and its security issues.